Financial Performance and Stock Prices of Top-Asset Conventional Banks Listed on the IDX (2019–2023) - Adyatma, Hardiyan; Nurhayati, Nurhayati; Purwanto, Dedik; Riswandi, Nairufar Rahmatika (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the effects of Net Interest Margin (NIM), Return on Assets (ROA), and Return on Equity (ROE) on the stock prices of conventional banks with the largest assets listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A total of 18 banks were purposively selected based on their market dominance and the availability of complete data. The research employed a quantitative approach using an explanatory method. A total of 90 annual observations were collected from financial statements published on the official IDX website. Data analysis was performed using SmartPLS software with the Partial Least Squares (PLS) method. The results show that ROA and ROE have a positive but statistically insignificant effect on stock prices—an interesting finding given the traditional importance of these ratios in evaluating financial performance. In contrast, NIM has a positive and statistically significant effect on stock prices, indicating that investors place greater emphasis on how efficiently banks generate net interest income. Together, the three variables account for approximately 41% of the variation in stock prices. These findings provide practical insights for investors and bank managers, highlighting the need to prioritize operational efficiency, which appears to have a greater influence on market perception than conventional profitability measures during the observed period.